COMPILATION OF A UNIFIED AND HOMOGENEOUS AEROMAGNETIC MAP OF THE GREEK MAINLAND - Chailas, S.; Tzanis, A.; Kranis, H.; Karmis, P. (Bulletin of the Geological Society of Greece, 2010)
We present a unified and homogeneous digital aeromagnetic map of the Hellenic mainland, based on the 1:50,000 map series of IGME. These maps cover the areas A1, A2, B, C1, C2, C3, D1 compiled by Hunting Geology and Geophysics Ltd. and measured at nominal ground clearances (flight altitudes) 150m AGL, 150m AGL, 300m AGL, and 2300m AMSL respectively (part of C2 with 3000m AMSL). We also include the entire area of Northern Greece, measured by ABEM AB with nominal ground clearance 275±75m AGL. The original map sheets were digitally imaged, georeferenced, digitized along contour lines and interpolated onto regular 250´250m grids. The unified aeromagnetic map was constructed by collating the mosaic of the resulting gridded data. Using upward/ downward continuation techniques various homogeneous versions of the map, were compiled by referencing of the observed mosaic total magnetic field to a unique constant ground clearance or to a unique constant elevation above mean sea level. This is the first time there is a complete and unified image of the magnetic signature of the isopic zones and rock formations comprising the Hellenic mainland, with particular reference to the ophiolite suites, which provides additional insight into the Alpine and post-alpine tectonics of the area.